ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI NASABAH PERBANKAN SYARIAH - Tukirin, Tukirin (MAJALAH ILMIAH WIDYA, 2012)
The Islamic banking has demonstrated its superiority in the storms of the world monetary crisis of 1997-1998. But in its development of Islamic banks is still a alternaif in stimulating the economy and society can not become the main actors. The objective of this article is to study the reviewing results of related research publications in international journals of Islamic banks. The method used library reseach and analized descriptively. It can be concluded that it was found that Islamic banks have not been efficient, the Muslim community has realized that religion is the reason for the selection of banks different from the non-Muslim societies. On the whole Muslim community and non-Muslims to make the quality of service by the employee and the proximity of service facilities into consideration in choosing a bank. While non-Muslim society makes the interest rate becomes an important reason in saving money or making deposits in banks.